2019
DOI: 10.3389/fpls.2018.01929
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Molecular and Genomic Techniques for Biodiversity Research and DNA Barcoding of the Arabian Peninsula Flora

Abstract: The Arabian Peninsula is known to have a comprehensive and rich endowment of unique and genetically diverse plant genetic resources. Analysis and conservation of biological diversity is a crucial issue to the whole Arabian Peninsula. The rapid and accurate delimitation and identification of a species is crucial to genetic diversity analysis and the first critical step in the assessment of distribution, population abundance and threats related to a particular target species. During the last two decades, classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 170 publications
0
26
0
Order By: Relevance
“…A plant metabarcoding study of eDNA extracted from soil concluded that rbcL and ITS2 provided better taxonomic resolution and had more complete reference databases—although this will vary by region—than either matK or the trnL P6 loop (Fahner et al., 2016). However, some barcoding studies have found greater species resolution from matK compared to either ITS2 and rbcL (Mosa et al., 2019), or to rbcL and trnH‐psbA (Scriver et al., 2015). Additionally, no single marker has revealed a barcoding gap, in which interspecific sequence divergence consistently exceeds intraspecific sequence divergence, across all plant taxonomic comparisons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plant metabarcoding study of eDNA extracted from soil concluded that rbcL and ITS2 provided better taxonomic resolution and had more complete reference databases—although this will vary by region—than either matK or the trnL P6 loop (Fahner et al., 2016). However, some barcoding studies have found greater species resolution from matK compared to either ITS2 and rbcL (Mosa et al., 2019), or to rbcL and trnH‐psbA (Scriver et al., 2015). Additionally, no single marker has revealed a barcoding gap, in which interspecific sequence divergence consistently exceeds intraspecific sequence divergence, across all plant taxonomic comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no single marker has revealed a barcoding gap, in which interspecific sequence divergence consistently exceeds intraspecific sequence divergence, across all plant taxonomic comparisons. ITS might be more likely to show a gap than the commonly used plastid markers (Gill et al., 2019; Kuzmina et al., 2018), although this can be influenced by factors such as the relatedness of the taxa being compared (Gill et al., 2019) and the biogeographic region under consideration (Mosa et al., 2019). There is a clear lack of consensus on the most useful markers for plant barcoding and metabarcoding.…”
Section: Introductionmentioning
confidence: 99%
“…So, best-suited molecular assay for fingerprinting and assessing genetic relationship among genotypes shows their own advantages and limitations. In this sense, among the available biotechnological analysis of plant genetic diversity and DNA fingerprinting still not available an ideal technique that had yet fulfil all requirements needed by plant researchers [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Advantages Disadvantages References Next-generation sequencing (NGS) (i) No prior sequence information or probe generation is required (i) High in cost and not available in all laboratories (ii) Time-consuming and high data store required [55] Simple sequence repeats (SSR) and intersimple sequence repeats (ISSR) (i) Readily use for taxonomic studies (i) Allele sizes often differ from different laboratories Lack of potential in discriminating species in hypervariables (ii) Occurrence of null alleles complicate the interpretation of data because heterozygotes cannot be identified, and reaction failures cannot be detected [56,57] Amplified fragment length polymorphism (AFLP) (i) No prior sequence information or probe generation is needed (i) AFLP generates huge quantities of information technically demanding in the laboratory and, especially, in data analysis (ii) Interspecies genetic hybrids in the genus are difficult to identify [58] Random amplified polymorphic DNA (RAPD) (i) Producing DNA patterns that allow comparison of many loci simultaneously (i) Low cost (i) It may not be practical to identify the species of origin in products containing mixtures of species (ii) It does not seem to be adequate for analysis of severely degraded material, as in autoclaved samples [59,60] e Scientific World Journal utilizing their unique natural resources and traditional indigenous knowledge and thus not being a pray of corporate hijacking.…”
Section: Methodsmentioning
confidence: 99%